Aplikasi Herbisida Berbahan Aktif Campuran Atrazin-Mesotrion dan Paraquat dalam Pengendalian Gulma pada Pertanaman Jagung (Zea mays L.) - Rima Esa Lolitasari; Saifuddin Hasjim (Fakultas Pertanian Universitas Jember, 2019)
Corn in cultivation is inseparable from several other organism disorder s that can inhibit or reduce that productivity. One of the disorders is caused by weeds. Application of herbicides with active ingredients on the mixture of atrazine-mesotrion, and paraquat which is applied to corn plants has its own effect on corn plants if it is applied not according to the time or recommended dosage. The experimental design used, namely Randomized Completely Block Design (RCBD) with 6 treatments and 4 replications, namely P0 (control or uncontrolled), P1 (manual weeding 21 hst and 42 hst), P2 (Application of atrazine a nd mesotrione dose of 1.5 l / ha 21 hst), P3 (Application of paraquat dose 1 l / ha 21 hst), P4 (Application of atrazine and mesotrione dosage 1.5 l / ha 21 hst and 42 hst), P5 (Application of paraquat dose 1 l / ha 21 hst and 42 hst). The results showed that the use of herbicides with active ingredients atrazine, mesotrione, and paraquat had been able to effectively reduce the biomass of broad-leaf weeds and grasses. The use of the paraquat active ingredient applied at 21 hst showed the highest phytotoxicity symptoms in weeds and in maize plants. The use of two active ingredients of herbicide, manual weeding and control had no effect on plant height, growth rate, cob length, ear circumference, and had effect on shell weight.